PERTANGGUNGJAWABAN PIDANA KORPORASI YANG MELAKUKAN KORUPSI PENGADAAN BARANG DAN JASA - Marthin Simangungsong; Sihol Marito Siregar (Magister Hukum Universitas HKBP Nommensen, 2021)
A corporate criminal accountability is a corporate obligation to receive a reply for his crimes. These crimes can be appealed to corporations based on theories about how they handle criminal crimes. The study is aimed at understanding the form of corporate criminal accountability under the law no. 31 in 1999, Jo law no. 20 in 2001 on the elimination of corruption crimes, and understanding the corporate criminal accountability of those who are in the corruption management of goods and service ruling no.1 / ppd. SUS/ppd. PST. This study is a normative-law study, with legal sources being primary and secondary legal materials, with regulatory and case approaches, and is then studied descriptively by using deductive and inductive methods to address the problem. Based on research the authors conducted on corporate criminal accountability that underlie the 51st/pd. SUS/tipikor /2018/ pk. JKT. In the first semester of 2008, bank Indonesia the central bank/bi decided to raise its key rate by 25 basis points to 8.25 percent in the second quarter of this year.